PERSEPSI MASYARAKAT DESA BOKAK SEBUMBUN TERHADAP KEBERADAAN TAMAN KEANEKARAGAMAN HAYATI DI KECAMATAN SEKADAU HILIR KABUPATEN SEKADAU - Murniatun, Murniatun; Zainal, Sofyan; Idham, M (JURNAL HUTAN LESTARI, 2019)
Indonesia is a country that has a very diverse wealt in the from of the beuty of flora and fauna ecosystems and natural phenomena. Given the importance of forests to people’s lives both directly and indirectly, forest esources must be managed properly. One of these is natural resources the biodiversity park. The biodersity park is a reserve area of biological natural resource of local outside the forest area that has ex-situ and in-situ conservation, especially for plants that are pollinated or the locator is assistend bay animals with the composition and structure of vegetation that can suport the pollinator and scatter conservation seeds, there for the maintenance in biodiversity park. Therefore this study aims to examine the comunity perceptions of Bokak Sebumbun Village on the exsistence of he biodiversity park in Sekadau Hilir Subdistrict and to analize he relationship of age, knowlage and cosmopolitan factor from the perception of the Bokak Sebumbun Village to the exstence of biodiversity Parks. This study used an interview technique research method for 84 respondents to the head of the family in Bokak Sembumbun Village. Examples of respondent were conducted using purposive sampling technique. Data analysis using descriptive and inferential data analysis from the Kendall Tau correlation. The results show that people perceptions Bokak Sebumbun Village of existence biodiversity parks tend to be natural, because people basically realize that they depend on the surrounding biodiversity park. However, the comunity does not understand how to manage sustainably so that the benefits are sustainable. Keywords: Perception, Bokak Sebumbun, Biodiversity Park.